(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To validate the content of an instrument for nursing consultation with people with venous ulcers. Methodology: Methodological study of internal validation of content based on the judgment of enterostomal therapist judges, whose identification occurred through a search on the Lattes Platform. The process occurred in the months of January and February 2019 and 24 experts participated. Data regarding the evaluation of the query were compiled in Microsoft Office Excel spreadsheet and considered according to total and global agreement index, totaling 209 items and 2,400 variables of the query, dichotomous responses being adopted. Results: Regarding the characterization of the judges, a mean age of 36.6 years was obtained. Most were female and located in the state of Ceará. The main qualification observed was Master’s degree (62.5%) and the judges worked in assistance and coordination of enterostomal therapy services. Two thirds had experience with validation of instruments (66.7%). Regarding the validation of the consultation, an overall agreement index of 92% and an alpha of 0.91 were obtained. Conclusion: The consultation has an adequate appearance to be used, is easy to apply, has a logical sequence, and enables a systematic nursing care.